(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
The persistence of drug-resistant microorganisms in environmental water sources, particularly boreholes, presents growing challenges for public health, especially within densely populated urban locales. In Kaduna Metropolis, borehole water serves as a crucial means of potable water supply; however, the infiltration of bacteria with antibiotic resistance into these sources represents a concerning vector for advancing antimicrobial resistance (AMR). This investigation explored the genetic mechanisms of bacterial strains retrieved from borehole water across four administrative districts Chikun, Igabi, Kaduna North, and Kaduna South spanning dry and wet climatic periods. A cumulative total of 200 samples were acquired and subjected to bacteriological assessment using established culture-based methodologies. Polymerase Chain Reaction (PCR) techniques were utilized to screen for specific resistance-related genes, including blaTEM, gyrA, sul1, and PBP2a. Molecular screening identified multiple resistance determinants, with sul1 being the most frequently encountered. These findings point to the role of borehole water systems in harboring resistant microbial populations and underline environmental contributions to AMR transmission. The identified geographical and seasonal disparities in bacterial occurrence further emphasize the impact of regional infrastructure and environmental dynamics, reinforcing the call for sustained monitoring and proactive public health strategies, even in the absence of seasonal or locational trends in resistance behavior.